2007
DOI: 10.1074/jbc.m610875200
|View full text |Cite
|
Sign up to set email alerts
|

Heteromeric Assembly of Human Ether-à-go-go-related Gene (hERG) 1a/1b Channels Occurs Cotranslationally via N-terminal Interactions

Abstract: Alternate transcripts of the human ether-à-go-go-related gene (hERG1) encode two subunits, hERG 1a and 1b, which form potassium channels regulating cardiac repolarization, neuronal firing frequency, and neoplastic cell growth. The 1a and 1b subunits are identical except for their unique, cytoplasmic N termini, and they readily co-assemble in heterologous and native systems. We tested the hypothesis that interactions of nascent N termini promote heteromeric assembly of 1a and 1b subunits. We found that 1a and 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
75
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(83 citation statements)
references
References 64 publications
8
75
0
Order By: Relevance
“…That this ER motif cannot be masked by coassembly with other Kv11.1b subunits, but can be when expressed with the ⌬2-135 construct, suggests that it is the proximal N-terminal domain in Kv11.1a (or ⌬2-135) that binds the ER retention motif in heterotetrameric channels. This is also consistent with the finding from Phartiyal et al (33) who showed that the N-terminal regions of Kv11.1a and Kv11.1b are sufficient for interaction. In the case of the Kv11.1-3.1 isoform, the last 33 residues of the PAS domain are present (21 of these residues are hydrophobic), which we suggest are unlikely to fold into a compact structure and so are more likely to be recognized as unfolded and be tagged for degradation.…”
Section: Discussionsupporting
confidence: 93%
“…That this ER motif cannot be masked by coassembly with other Kv11.1b subunits, but can be when expressed with the ⌬2-135 construct, suggests that it is the proximal N-terminal domain in Kv11.1a (or ⌬2-135) that binds the ER retention motif in heterotetrameric channels. This is also consistent with the finding from Phartiyal et al (33) who showed that the N-terminal regions of Kv11.1a and Kv11.1b are sufficient for interaction. In the case of the Kv11.1-3.1 isoform, the last 33 residues of the PAS domain are present (21 of these residues are hydrophobic), which we suggest are unlikely to fold into a compact structure and so are more likely to be recognized as unfolded and be tagged for degradation.…”
Section: Discussionsupporting
confidence: 93%
“…In cells, the 1a N-terminal fragment can disrupt 1b subunit homo-oligomerization and core glycosylation. Because core glycosylation occurs cotranslationally (21,22), these observations suggest the two subunits associate via N-terminal interactions early in biogenesis (20). Such a cotranslational interaction implies that the 1a and 1b mRNA transcripts and their respective polysomes must be located in close physical proximity to each other.…”
mentioning
confidence: 95%
“…The assembly of hetero-oligomeric hERG 1a/1b channels has been suggested similarly to involve cotranslational, cytosolic N-terminal interactions between subunits (20). In this case, the hERG 1a and 1b N termini are structurally distinct, but were shown to interact in a dose-dependent manner in vitro.…”
mentioning
confidence: 99%
“…Overall, we propose that, similar to the formation of heterooligomers by hErg 1a and 1b (34), the subfamily recognition procedure for ether-à-go-go K ϩ channels takes place early in the biogenesis process. This subunit recognition task may require concerted interactions of N/C-terminal subfamily-specific sequences, such as the previously identified tetramerizing coiled-coil structure in CAD/TCC (14,15).…”
Section: Discussionmentioning
confidence: 74%
“…Despite sharing homologous cap sequence and PAS domain (collectively known as the eag domain), Eag and Erg significantly differ in the length of the N-linker, with the latter being about 190 amino acids longer. Importantly, hErg 1a (the hErg clone employed herein) and the truncated hErg 1b, two isoforms with a size difference of more than 300 amino acids in the N terminus (32,33), have been shown to form hetero-oligomers mediated by N-terminal interactions (34), raising the possibility that hErg channels may contain certain N-terminal assembly domains. Furthermore, the hErg PAS (eag) domain was suggested to regulate deactivation kinetics via intersubunit interactions (26).…”
Section: Resultsmentioning
confidence: 99%